"Neuro-psycho-BS": A Case Report of Rare Association with Bipolar Disorder. Issue 1 (25th July 2018) - Ali, Mustafa; Das, Soumitra
Abstract : Bechet's Disease is an inflammatory disease characterized by recurrent oral ulcers (OU), genital ulcers (GU) and uveitis which can develop a neurobehavioral syndrome, also defined as 'neuro-psycho- BS'. Depending on vascular or parenchymal lesions, the presentations could be varied. Due to sparse literature, there is no consensus on management of psychiatric illness comorbid with Bechet's disease. Bipolar disorder in Bechet's disease is extremely rare. Here, we are presenting a case of episodic exaggeration of Bipolar disorder along with Bechet's disease which imposed both clinical and management challenges.